Compliance with IAS 2 in consolidated financial statements of PSE listed companies - Kateřina Polachová (European Financial and Accounting Journal, 2019)
As inventories represent a significant balance sheet item for many companies, their correct presentation and disclosure is fundamental for the financial statements' users. This article identifies compliance with the 'IAS 2 Inventories' requirements in consolidated financial statements of selected Czech companies. After determining criteria for the issuer's sample, two research questions were set up for the evaluation of compliance measures with IAS 2. The research focuses on the association between the sum of total assets and the sum of inventories as well as an association between the sum of inventories and their allowances. Investigation is followed by the determination of compliance or non-compliance with the requirements of IAS 2. The research leads to the conclusion that the sum of inventories depends on the sum of assets. However, the sum of inventories' allowances does not depend on the sum of inventories. As far as the area of compliance with the IAS 2 requirements is concerned, on average, issuers did not comply with 3 out of total 8 IAS 2 requirements. The most problematic area of compliance was how reversals of write-downs were disclosed. The second most problematic requirement was a write-down justification and the third most problematic requirement was a disclosure of pledged inventories.
Keywords: M41; 650; IAS 2; inventories; allowances; IFRS disclosure